2011
DOI: 10.1117/1.3662448
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of within-individual fluctuation of depressed mood with prefrontal cortex activity during verbal working memory task: optical topography study

Abstract: Abstract. Previous studies showed that interindividual variations in mood state are associated with prefrontal cortex (PFC) activity. In this study, we focused on the depressed-mood state under natural circumstances and examined the relationship between within-individual changes over time in this mood state and PFC activity. We used optical topography (OT), a functional imaging technique based on near-infrared spectroscopy, to measure PFC activity for each participant in three experimental sessions repeated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 39 publications
1
34
1
Order By: Relevance
“…To better understand the mood–cognition interaction in the PFC, we previously introduced a new approach which focused on the natural mood state in healthy participants without using a mood-induction method (Aoki et al, 2011, 2013; Sato et al, 2011). In these studies, a psychological questionnaire (Profiles of Mood States, POMS) (McNair et al, 1971; Yokoyama et al, 1990) was administered to assess the participants' natural moods during the past week, and near-infrared spectroscopy (NIRS)—a non-invasive and less body-constraint neuroimaging technique (Maki et al, 1995; Koizumi et al, 2005; Ehlis et al, 2014)—was used to measure their PFC activity during an emotionally-neutral delayed match-to-sample verbal/spatial WM paradigm (Smith et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the mood–cognition interaction in the PFC, we previously introduced a new approach which focused on the natural mood state in healthy participants without using a mood-induction method (Aoki et al, 2011, 2013; Sato et al, 2011). In these studies, a psychological questionnaire (Profiles of Mood States, POMS) (McNair et al, 1971; Yokoyama et al, 1990) was administered to assess the participants' natural moods during the past week, and near-infrared spectroscopy (NIRS)—a non-invasive and less body-constraint neuroimaging technique (Maki et al, 1995; Koizumi et al, 2005; Ehlis et al, 2014)—was used to measure their PFC activity during an emotionally-neutral delayed match-to-sample verbal/spatial WM paradigm (Smith et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These aforementioned tasks are used in brain-computer interface (BCI) and attention studies [44][45][46][47][48]. More recently, fNIRS has been accepted as an assistive tool to differentiate depression, bipolar and schizophrenia [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to the MDD patients, schizophrenia and prefrontal-lesioned patients showed pronounced attenuation of the P3b latency shift and the differential processing between the two target conditions, demonstrating an impaired ability to utilize predictive local context (Fogelson et al, 2009a(Fogelson et al, , 2011b. There is evidence for the role of the prefrontal cortex and prefrontal networks in depression (Bench et al, 1992;Pascual-Leone et al, 1996), and prefrontal network dysfunction in depressed patients has been associated with working memory deficits (Pu et al, 2011;Sato et al, 2011;Price and Drevets, 2012). Thus, it is likely that the deficits in processing local contextual information observed in the MDD patients in the present study may also be related to prefrontal or prefrontal network dysfunction.…”
Section: Altered Processing Of Predictive Local Context In Depressionmentioning
confidence: 91%
“…Performance on measures of executive function tend to be impaired in depressed patients, and working memory deficits are common (Pelosi et al, 2000;Rose and Ebmeier, 2006;Segrave et al, 2010;Marazziti et al, 2010;Sato et al, 2011) and associated with impairments in attentional control (Pelosi et al, 2000;Rose and Ebmeier, 2006;Segrave et al, 2010;Gotlib and Joormann, 2010;Murrough et al, 2011). However, other studies have demonstrated that there are no impairments in working memory functions in patients with depression (Barch et al, 2003;Holmes et al, 2005).…”
Section: Introductionmentioning
confidence: 93%